Development of a patient reported outcome measures for measuring the impact of visual impairment following stroke - Lauren R. Hepworth; Fiona J. Rowe; Girvan Burnside (BMC, 2019)
Abstract Background Among the available patient-reported outcome measures (PROMs) there is an absence of a PROM with a specific focus on the impact of the wide variety of visual impairments following stroke. Our aim was to develop a patient reported quality of life outcome measure for stroke survivors with visual impairment. Methods Potential items were sourced from a combination of existing PROMs from a systematic review and qualitative in-depth interviews, duplicates were removed and items shortlisted. The initial pilot instrument was created following a ranking exercise of these potential items and consultation with stroke survivors. Version 1 was piloted with 37 stroke survivors at acute and chronic stages. Version 2 was piloted with 243 stroke survivors with visual impairment at acute and chronic stages. This data was analysed using the Rasch measurement model. Simultaneously, items from Version 2 underwent a Delphi process with stroke survivors and stroke clinicians, to assess the importance of each item. Final consensus decisions on item removal were made using the combined analysis from the Rasch measurement model and Delphi process in a nominal group meeting. Results Due to the wide range of rank given to the majority of categories/items, only two items were discarded. Version 1 comprised of 102 items with 5 response categories relating to amount of difficulty. The pilot of Version 1 allowed item reduction based on analysis of floor/ceiling effects and not applicable responses. Version 2 comprised of 62 items. Within the nominal group meeting, the expert panel created a set of rules which aided them with decision making in addition to the Rasch and Delphi analysis data. This resulted in the removal of 43 items and the combination of seven items to create three new items. The expert panel also recommended the rewording of three items. Conclusion The Brain Injury associated Visual Impairment Impact Questionnaire (BIVI-IQ-15), a 15-item instrument with 4 response categories has been developed for capturing vision-related quality of life of stroke survivors with any of the predominant types of visual impairment, in the presence of other impairments and for both inpatients and outpatients.